2009
DOI: 10.3109/15376510903401708
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of aldehyde dehydrogenase 2 (Aldh2) knockout mice

Abstract: Acetaldehyde is an intermediate of ethanol oxidation. It covalently binds to DNA, and is known as a carcinogen. Aldehyde dehydrogenase 2 (ALDH2) is an important enzyme that oxidizes acetaldehyde. Approximately 45% of Chinese and Japanese individuals have the inactive ALDH2 genotypes (ALDH2*2/*2 and ALDH2*1/*2), and Aldh2 knockout mice appear to be a valid animal model for humans with inactive ALDH2. This review gives an overview of published studies on Aldh2 knockout mice, which were treated with ethanol or ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Homozygous mice were born at the expected Mendelian ratios and show no overt phenotype ( Supplementary Fig. 3c), consistent with previously published Aldh2 knockout mice 23 . Second, we crossed Aldh2 2/2 with Fancd2 1/2 mice made in the 129S4 background 24 .…”
Section: Fanconi B Cells Are Sensitive To Acetaldehydesupporting
confidence: 87%
“…Homozygous mice were born at the expected Mendelian ratios and show no overt phenotype ( Supplementary Fig. 3c), consistent with previously published Aldh2 knockout mice 23 . Second, we crossed Aldh2 2/2 with Fancd2 1/2 mice made in the 129S4 background 24 .…”
Section: Fanconi B Cells Are Sensitive To Acetaldehydesupporting
confidence: 87%
“…This causes the "alcohol flushing" syndrome characterized by the reddening of the face, neck, and, in some cases, the entire body due to dilation of capillaries (Eriksson, 2001). Similar elevations in acetaldehyde have been observed in the Aldh2-null mice (Yu et al, 2009). The second enzyme involved in acetaldehyde metabolism is ALDH1A1.…”
Section: Introductionmentioning
confidence: 53%
“…Another study reported that the dynamic expression of ALDH1B1 correlated with granulocytic development of hematopoietic stem cells; in this report, the author proposed a possible role of ALDH1B1 in retinoic acid metabolism mediating the effect (Luo et al, 2007). A transgenic mouse line having forced expression of the human ALDH2*2 variant exhibited distinct phenotypes, including small body size, reduced muscle mass, diminished fat content, and osteopenia (Endo et al, 2009), all of which are absent from ALDH2-null mice (Yu et al, 2009). One hypothesis to explain such a discrepancy is that the ALDH2*2 mutant subunit not only inactivates the ALDH2 wild-type subunit but also inactivates other ALDHs by forming heterotetramers, thereby blocking their functions.…”
Section: Initial Characterization Of Human Aldh1b1mentioning
confidence: 99%
See 1 more Smart Citation
“…The closest model to the human ALDH2*2 polymorphism is the Aldh2 knockout (KO) mouse, which expresses no protein or enzymatic activity (20). Although Aldh2 KO mice are useful for investigating the impact of complete lack of ALDH2 activity (21), they fail to faithfully reproduce the structural and biochemical properties of ALDH2*2 in human physiology and pathology (21)(22)(23). In particular, ALDH2*2 is expressed with reduced but not loss of enzymatic activity and increased protein turnover (24).…”
mentioning
confidence: 99%